The barriers in implementation of ISO 9001 quality management system standard in Somaliland for small and medium enterprises - Mohammed, Abdiaziz Farhan (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
In 2017 a total of 1,106,356 ISO 9001 certificates were issued worldwide. Only 13,378 were certified to African organizations. African continent lags in the implementation of the ISO 9001standard. The low number of certificates suggests the existence of barriers to the implementation of the standard. Number of studies were conducted to determine these barriers in several African countries. In Somaliland, there are no ISO 9001-certified organizations and there have been no studies done on factors preventing the implementation of the standard. Therefore, the purpose of this study is to determine barriers to ISO 9001 implementation in Somaliland SMEs and to develop a framework for the implementation process. The method of quantitative research was used, and a structured questionnaire was developed and delivered to a randomly selected 100 Somaliland SMEs. Out of the sample, a total of 86 questionnaires were returned, giving a final response rate of 86%. Five variables were determined from related literature to be the hindering variables to the implementation of ISO 9001 in most African countries. Findings reached from this research indicated three variables to account significant variance in barriers; government regulations (R2 = 0.35, p = .00), lack of leadership commitment (R2 = 0.20, p = .00), and lack of human resource (R2 = 0.30, p = .00), as the three major barriers to ISO 9001 implementation to SMEs in Somaliland. For the other variables measured they did not cause significant variance in the barriers. The awareness level of ISO 9001 standard among Somaliland SMEs is found to be moderate (M=3). This result concurs with the findings conducted in other countries. To overcome the identified barriers, the study proposes an ISO 9001 implementation framework. The framework is to assist Somaliland SMEs in improving their capability and thereby contribute to their competitive advantages. The objectives of this study were successfully achieved, three main barriers to ISO 9001 implementation to SMEs in Somaliland were identified and a framework taking these barriers into account was developed. This study builds the foundation for a better understanding of the quality management system in Somaliland. It also contributes to the body of knowledge in the area of the quality management system with interest in Somaliland. The findings and the developed framework of this study is limited by the geographical location of the study.